What’s Behind the Mask?: Understanding Stealth Practices of Grindr Users - Wesley-Smith, Ian N.; Chapin, W. E. (AoIR Selected Papers of Internet Research, 2016)
Grindr is a geo-social dating app for men seeking men. However, some men who create profiles on Grindr do not post identifiable pictures, a practice that seems at odds with the goal of finding a romantic partner. In order to understand why Grindr users choose unidentifiable pictures, we surveyed Grinder users asking for descriptions of and explanations for their choice of profile picture, as well as their perceptions of users who do not have an identifiable profile picture. We discovered that location was a factor in why some Grinder users displayed unidentifiable profile pictures, but other users change their profile from identifiable to unidentifiable as a means of controlling interactions.